Visualization of rapid electron precipitation via chorus element wave–particle interactions - Mitsunori Ozaki (Nature Portfolio, 2019)
Electron precipitation plays major role in magnetospheric physics and space weather. Here the authors show nonlinear behavior of the wave–particle interaction in the magnetosphere as the evolution of chorus electromagnetic waves detected by the Arase satellite and PWING observatory.